Long-term memory in epithelia: transient IFNγ exposure drives stable repression of TFF1 in gastric epithelial cells via epigenetic changes - Voli, Antonia; Eletto, Daniela; Mentucci, Fatima Maria; Centrella, Chiara; Pannetta, Martina; Boccellato, Francesco; Finizio, Alfonso; Morello, Silvana; Giraulo, Caterina; Porta, Amalia; Tosco, Alessandra (Frontiers in Immunology, 2026)
IntroductionInterferon-gamma (IFNγ) is a pro-inflammatory cytokine that is transiently produced and typically activates short-lived JAK–STAT1 signaling, yet it can also induce long-term transcriptional changes. During Helicobacter pylori infection, IFNγ persists in the gastric environment, contributing both to host defense and epithelial injury that promotes tumorigenesis. While long-term IFNγ memory has been described in immune cells, its impact on gastric epithelial reprogramming remains unclear.MethodsWe exposed gastric epithelial cells to brief IFNγ stimulation and analyzed gene expression, transcription factor involvement, and epigenetic modifications. Chromatin remodeling at the TFF1 locus was assessed through histone modification analyses, and the role of DNA methylation was evaluated using pharmacological inhibitors. Findings were validated in primary gastric mucosoids exposed to inflammatory mediators released by H. pylori-activated immune cells.ResultsTransient IFNγ exposure caused stable repression of TFF1, a gastric tumor suppressor frequently lost in H. pylori-associated cancer. This repression persisted after cytokine removal and was mediated by the IFNγ-responsive transcription factor C/EBPβ. Mechanistically, TFF1 silencing was associated with chromatin remodeling, including altered histone H3S10 phosphorylation and H3K9 acetylation at the TFF1 locus. Inhibition of DNA methylation prevented both TFF1 downregulation and C/EBPβ upregulation, indicating that de novo methylation stabilizes the silenced state. Similar durable TFF1 repression was observed in primary gastric mucosoids following exposure to inflammatory mediators.DiscussionOverall, our findings show that transient inflammatory signals cause durable gene silencing through epigenetic remodeling, revealing how chronic inflammation can reprogram epithelial cells and promote cancer, while suggesting strategies to reverse these effects.